Fournier's Gangrene Following Acute Gastroenteritis in a Female Infant - Muhammad Shakur Abubakar; Ibrahim Ahmadu; Suleiman Dada Aliyu; Oiza Ozioroko Aliu-Isah (Wolters Kluwer Medknow Publications, 2024)
Background: Fournier's gangrene (FG) is a rare necrotizing infection of the genital and perineal structures. It can be very fatal, especially when appropriate treatment is delayed. Clinical Description: A 17-month-old girl presented with acute diarrhea, fever, and perineal ulceration. The perineal ulcer started as reddish rashes on the 3rd day of diarrhea, which rapidly progressed to form a large ulcer the next day. She was critically ill and in heart failure at presentation. Management and Outcome: After stabilization, investigations and cultures were taken. She had hyponatremia, hypokalemia, and neutropenia. The wound swab and blood culture yielded Pseudomonas aeruginosa and coagulase-negative Staphylococcus aureus (methicillin resistant). She was treated with antibiotics, wound debridement and other supportive care. She recovered fully from her acute illness with complete healing of the ulcer. Conclusion: This case report brings to the fore the possibility that acute diarrhea in the presence of other predisposing factors may cause FG. Early recognition and prompt management by multidisciplinary team can result in successful outcomes.